Comprehensive analysis of the multifaceted role of ITGAV in digestive system cancer progression and immune infiltration - Shi, Xinyue; Zang, Jingyu; Gu, Qi; Zhang, Mengmeng; Sun, Handi; Yang, Lijun; Cheng, Jiahui; Wang, Ruonan; Mao, Han; Xu, Aitong; Wang, Xin; Xiao, Yu; et al. (Frontiers in Immunology, 2025)
BackgroundDigestive system cancers are among the most common malignancies, exhibiting consistently high incidence and mortality rates, yet effective detection and treatment targets remain limited. Integrin αv (ITGAV, CD51) is a significant member of the integrin family, widely recognized for its role in mediating interactions between cells and the extracellular matrix, as well as intracellular signaling. In recent years, ITGAV has been found to have significantly elevated expression in multiple tumors, such as prostate cancer, breast cancer, and osteosarcoma, and was considered to be a key component in various stages of tumor progression. However, no systematic digestive system cancer analysis has been conducted to explore its function in prognosis, diagnosis, and immunology.MethodsTranscriptome sequencing and clinical data of samples were obtained from The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression Project (GTEx), Human Protein Atlas (HPA), cBioPortal, TIMER and TISIDB databases. Bioinformatics methods were employed to investigate the potential oncogenicity of ITGAV, focusing specifically on the analysis of its prognosis, diagnostic value, and immune infiltration level of ITGAV in digestive system cancers. In addition, GO, KEGG, and PPI network analysis revealed the biological functions and related signaling pathways related to ITGAV. Finally, the role of ITGAV in regulating cancer progression was experimentally verified using hepatocellular carcinoma and pancreatic cancer as examples.ResultsWe found that ITGAV was highly expressed in multiple digestive system cancers. In addition, high expression of ITGAV was closely associated with poor prognosis and showed potential for early diagnosis. Enrichment of pathways related to extracellular matrix organizing processes and tumor migratory movements was identified. In vitro, results showed that the knockdown of ITGAV significantly inhibited the migratory movement ability of hepatocellular carcinoma and pancreatic cancer cells, while its overexpression significantly promoted the migration of the above cells. Finally, immunoassays showed a significant correlation between ITGAV expression and the infiltration level of various immune cells, further clarifying the critical role of ITGAV in the tumor immune microenvironment.ConclusionOur results elucidated the importance of ITGAV in the prognostic assessment, early diagnosis, and targeted immunotherapy of digestive system cancers, and revealed its multifaceted role in regulating cancer progression.